Vernachlässigt, aber unentbehrlich. Plädoyer für Vertrauen als Ressource in hybriden Lehr-/Lernbeziehungen an Hochschulen. - Brockmann, Nils Arne; Richter, Caroline (Das Hochschulwesen)
The guiding question of the plea is: What is the relevance of trust in teaching-learning relationships at universities, especially in hybrid spaces? This question is addressed by first presenting the third space as an actor in hybrid teaching-learning relationships, followed by an overview of the concept of "trust”, and finally, reflecting on experiences from practice. To conclude the plea, selected aspects of the discussion are condensed into two theses on trust in teaching-learning relationships. The article aims to raise awareness of the necessity to address trust relationships among third space personnel, teachers and students, which – in practical terms – is linked to the requirement of personal interaction experience and – in strategic terms – should be designed as a resource for university development.